SERANGAN PHISING WIFI MENGGUNAKAN ESP8266: REPLIKASI JARINGAN UNTUK PENANGKAPAN INFORMASI OTENTIKASI - Muhamad Nurdin; Ari Pranandi, Utari Dwi F, Yogi Hermawan, Riza Fadlapi (ADISAM PUBLISHER, 2024)
With the rapid growth of Internet of Things (IoT) technology and Wi-Fi networks as wireless communications infrastructure, information security is increasingly important in the digital environment. However, security attacks continue to grow. One of them is a Wi-Fi phishing attack, where attackers leverage Wi-Fi network replication to trick users and obtain their authentication information. The use of the ESP8266 module as a Wi-Fi network replication tool is an important issue that needs further review. The ESP8266 module can operate as a Wi-Fi access point or client within an existing Wi-Fi network. With its flexibility, this module can be leveraged to replicate legitimate Wi-Fi networks for phishing attacks. Wi-Fi network replication techniques typically involve masking the identity of a legitimate network, including SSID and other configuration, to trick users into connecting to a fake network. Attackers can exploit captive portals to request sensitive authentication information. These findings emphasize the importance of security awareness and the need for stronger precautions to protect users' personal data. The ESP8266 module successfully copies a Wi-Fi network using a legitimate SSID and tricks users into connecting to a fake network. Once connected, users are asked to enter a valid Wi-Fi password through the verification portal. Entered authentication information is logged for further analysis. Wi-Fi phishing attacks can result in the theft of personal information such as usernames, passwords, and financial information. The use of Wi-Fi replication can expose vulnerabilities in the security infrastructure and cause users to lose trust in public Wi-Fi networks. This study uses an experimental approach to investigate Wi-Fi phishing attacks using the ESP8266 module to replicate legitimate networks. Steps include creating a replica network, testing user connections, redirecting to captive portal, logging authentication information